2017
DOI: 10.1007/s41207-017-0033-x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of cryolite with high molar ratio from high fluorine-containing wastewater

Abstract: The recovery of fluoride from wastewater has great economic and environmental significance for the fluorine industry. Cryolite is an optimal product for fluorine recovery from high fluorine-containing wastewater. The cryolite with a high molar ratio is more valuable and is extensively used in the aluminum electrolytic industry. The present study aims to recover cryolite with a high molar ratio from high fluorine-containing wastewater through the crystallization process. The crystallization conditions of cryoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Although not as valuable as AlF3, cryolite is nonetheless a desirable commodity for Al smelting and indeed other uses outside the industry [80]. Unlike AlF3, it does not require a calcination step after precipitation, merely requiring drying at ~40C [10]. Al smelters have historically captured waste fluoride from the Hall-Heroult process as HF by caustic scrubbers and cryolite is attained from this feed by addition of Al2(SO4)3 [81].…”
Section: Pathways To Recovery Of Commodity Products From the Eluentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not as valuable as AlF3, cryolite is nonetheless a desirable commodity for Al smelting and indeed other uses outside the industry [80]. Unlike AlF3, it does not require a calcination step after precipitation, merely requiring drying at ~40C [10]. Al smelters have historically captured waste fluoride from the Hall-Heroult process as HF by caustic scrubbers and cryolite is attained from this feed by addition of Al2(SO4)3 [81].…”
Section: Pathways To Recovery Of Commodity Products From the Eluentmentioning
confidence: 99%
“…The main component of the Hall-Hèroult electrolysis bath is cryolite (Na3AlF6), which is increasingly a by-product of modern Al smelters, rather than consumed as a raw material [9]. It is nonetheless a valuable commodity chemical and still purchased in large quantities by the industry globally [10]. The market prices for AlF3 and cryolite, which are both produced from fluorspar, are on global long-term upwards trends, due to continued high demand and inefficient fluorine recycling [11].…”
Section: Introductionmentioning
confidence: 99%
“…The literature is somewhat diverse on this point. Chen et al reported that, at a 1:1 ratio, aluminium hydroxyfluoride precipitation dominates over cryolite, although only at pH 5.5 [49], whereas Jiang and Zhou predicted favourable cryolite recovery at the same ratio at pH 9 [50] and Wang et al demonstrated success using a F − /Al 3+ molar ratio 27.9 ± 0.6 of ~ 1:2.55 (although this was achieved by neutralisation of an acidic starting solution) [51]. We have considered the molar ratio monitoring and potential adjustment in previous work [29].…”
Section: La-mts9501 Column-elution Behaviourmentioning
confidence: 99%
“…So far, the focus of researchers has been mainly on three aspects of resource recovery: (1) the recovery of one single resource such as phosphorous [16][17][18], nitrogen [19], energy [20,21], metals [22] or specific components such as cryolite [23], mercury (Hg), and lead (Pb) [24]; (2) the increase of the recovery effectiveness of components; and (3) the technologies of component recovery such as struvite crystallization for phosphorous recovery [25] or microbial fuel cells technology for nitrogen recovery [26]. Energy recovery through anaerobic digestion of sewage sludge from biological wastewater treatment is state of the art [1].…”
Section: Introductionmentioning
confidence: 99%